Evidence for a Discrete Binding Protein of Plasminogen Activator Inhibitor in Plasma - Wiman, Björn; Lindahl, Tomas; Almqvist, Åsa (Thrombosis and Haemostasis, 1988)
Gel-filtration experiments of mixtures of functionally active and inactive forms of plasminogen activator inhibitor (PAI) with human plasma or bovine serum albumin have provided evidence for the existence of a discrete binding protein of PAI in plasma. Most likely it is a glycoprotein with a molecular weight of approximately 150,000. The data suggest that it forms a very stable complex with functionally active forms of PAI, but not with the inactive or “latent” PAI. However, the PAI activity seems not to be significantly altered by the interaction with the binding protein. Assuming that a stoichiometric complex is formed, titration experiments suggest that a pool of normal human plasma contains about 40–50 mg of PAI-binding protein liter.
Keywords: Plasminogen activator inhibitor (PAI); Protein-protein interaction; PAI-binding protein